Modeling thermal inactivation of Salmonella Typhimurium in mash broiler feed - T.P. Boltz (Elsevier, 2021)
SUMMARY: Feed hygienics is of increasing concern for poultry producers. This project included 2 studies to investigate kinetic parameters for inactivation of Salmonella Typhimurium in mash broiler feed heated at various temperatures. In study one, 2- and 5-g feed samples, contained in a sample bag, were inoculated with S. Typhimurium and submerged in a water bath heated to 90°C until internal temperatures of 75°, 80°, and 85°C were reached. In study two, 2-g of sample were inoculated with S. Typhimurium and submerged into a water bath set at 75°, 80°, 85°, 90°, and 95°C heated for 0 to 180 s. Feed sample and water bath temperature were monitored by thermocouples. Thermocouple data demonstrated 2- and 5-g samples achieved a 5-log reduction of S. Typhimurium when internal temperature of feed reached 80°C and 85°C, respectively. D-values for linear and Weibull models were calculated for the 5 temperatures. D-values of the linear model were 6.70, 8.83, 12.05, 13.91, and 24.40 s, and D-values for the Weibull model were 2.27, 3.67, 3.95, 4.68, and 7.63 s when heated to 95°, 90°, 85°, 80°, and 75°C. Individual temperature datasets were further analyzed using GinaFit software. As heating temperature decreased, Double-Weibull and Biphasic models fit all the thermal data, indicating that Salmonella could have generated 2 subpopulations with different thermoresistance. Similar to other thermal inactivation models, this study demonstrates that linear, Weibull, Double-Weibull, and Biphasic models could be used to predict thermal inactivation of Salmonella in mash broiler feed. These data may contribute to establishing feed mill microbiological safety standards and reducing Salmonella contamination in broiler feed.